EVALUASI PROGRAM PEMBELAJARAN SEJARAH PADA MADRASAH ALIYAH NEGERI (MAN) DI KOTA PEKANBARU - Zulfa Hendri; Kurniawati Kurniawati; Umasih Umasih (Universitas Negeri Malang, 2020)
Abstract: The purpose of this research was to determine how the implementation of the teaching of history in schools (Madrasah Aliyah Negeri) MAN 1 and 4 of Pekanbaru. The research method used in this study is amixed methodology. Mixed methods produce more comprehensive facts in researching research problems, because this researcher has the freedom to use all data collection tools according to the type of data needed. The analysis technique uses a qualitative data analysis approach carried out interactively and continues continuously until completion. Activities in this data analysis include data reduction, data display, and conclusion drawing / verification. The results of this study using the EKOP model on (1) Evaluation of the quality of learning among Teachers in the Classroom Performance is already good with maximum score results above 80.00%, Learning Facilities are quite above 60.00%, Class climate is enough above 60.00%, Learning Attitudes are quite good above 70.00%, and (5) Student learning motivation in student learning is quite good above 70.00%. Furthermore, the evaluation of learning outputs in terms of academic skills, which are taken from the results of formative and summative tests in both madrasas are also quite good. The average score raport of the Mapel History in MAN 1 was 84.34, while in MAN 4 Pekanbaru City it was 82.08. Thus it can be concluded that the evaluation of history learning programs in Madrasah Aliyah Negeri (MAN) in Pekanbaru City by using the EKOP learning model is very effective for evaluation of learning in schools.